Affordable digital electronics for building a hybrid dynamic marker structure with infrared illumination light patterns - Serrano-Pérez, Edgar; Soberanes-Martín, Anabelem (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
This work deals with the integration of low-cost electronic devices that were integrated into constructing a dynamic maker that allows the triggering of augmented reality events. A hybrid structure was developed to combine the most favorable aspects of fiducial markers and dynamic markers. The lighting infrared patterns are effectively modifiable through the programming of an ESP8266 microcontroller card. To test the system, an infrared lighting pattern generated was detected through a digital camera, and an augmented reality application was implemented using a web page for displaying text. Electronic shift registers were used for the temporal storage of the infrared illumination pattern. The infrared illumination marker can’t be detected by human eyes, but it is easily recognized due to the inner black square shape embedded into a white wooden structure.